UI/UX Design of the Mobile Application 'Kalem' Using the Double Diamond Method - Rembulan Cahyaninghati; R.M Chairil Andri; Nurul Aslamiah Istiqomah (ENCRYPTION: Journal of Information And Technology, 2024)
Abstract This research aims to design a user interface (UI) for a mobile application named "Kalem" to assist users in tracking their menstrual cycles and to analyze user experience (UX). The Double Diamond methodology, encompassing the Discover, Define, Develop, and Deliver phases, was employed to ensure a comprehensive approach to UI/UX design. The design process commenced with the Discover phase to identify user needs and problems. Subsequently, the Define phase was used to formulate the primary problem and requirements that the application must fulfill. In the Develop phase, design ideas were developed into testable prototypes. Finally, the Deliver phase resulted in a final prototype ready for user testing. The usability testing phase utilized the System Usability Scale (SUS) to measure and assess the ease of use and satisfaction of users. Based on the SUS calculation, the obtained score of 86.0753 indicates a positive result, placing the Kalem application design in the 'acceptable' category, suggesting that users are satisfied with its usability.